Analisis Miskonsepsi Materi Gaya dan Gerak Mata Pelajaran Ipas Pada Siswa Kelas IV MI Ma’Arif Mangunsari : Penelitian - Nur Aini Intan Hasanah; Khoirun Nisa’; Luthfi Sekar Nismara; Wulan Izzatul Himmah (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to analyze students’ misconceptions on the topic of temperature and heat using the Certainty of Response Index (CRI) model as a diagnostic tool. The research employed a quantitative descriptive approach involving a multiple-choice test accompanied by CRI scales to identify not only incorrect answers but also the confidence level behind each response. Data analysis included calculating the proportion of correct and incorrect answers, average CRI scores, and categorizing students into groups of scientific conceptions, misconceptions, or lack of knowledge. The results showed that several students selected incorrect answers with high CRI values, indicating strong misconceptions that must be addressed through targeted instructional strategies. Meanwhile, students with incorrect answers but low CRI scores were categorized as having a lack of knowledge rather than misconceptions. The findings highlight that misconceptions occurred most frequently in indicators related to heat transfer, the relationship between temperature and molecular motion, and factors affecting changes in temperature. The study concludes that CRI is an effective diagnostic method for distinguishing levels of student understanding and is useful for informing remedial instruction. These findings provide meaningful insight for ededucators in designing better learning interventions to reduce misconceptions.